ANALISIS PENGGUNAAN ANTIBIOTIKA PARENTERAL PADA PASIEN BRONKOPNEUMONIA DI RUANG RAWAT INAP PENYAKIT DALAM RSUP DR. M. DJAMIL PADANG - Ramadheni, Putri (Universitas 17 Agustus 1945 Jakarta, 2018)
Parenteral drug is often used because of its effect appears faster than peroral drug use. There has been evaluation for parenteral drug to bronchopneumonia in internal medicine ward at DR. M.Djamil hospital through observational method by porspective approach from May-Juli 2014 based on rational use and provision of parenteral antibiotic preparation. Based on its result, there is no incorrect drug use, antibiotic use is suitable to Bronchopneumonia antibiotic, 44,64% combination of two antibiotics or more, found two antibiotics is used together where as its class and mechanism are same is found where the most used is cephalosporin class III (65,15%). In plementation of pharmaceutical preparation is good, however the aseptic technique is les attention.